KEMAMPUAN NUMERASI PESERTA DIDIK MELALUI IMPLEMENTASI BLENDED LEARNING PADA MATERI BILANGAN PECAHAN - Lestari, Ayu; Hapizah, Hapizah; Mulyono, Budi; Susanti, Ely (Jurnal Pendidikan Matematika (JUPITEK), 2022)
This study aims to describe the numeracy skills of students in the matter of fractional arithmetic. This research method is a type of combination research. The research subjects were 31 students of class VIIU1 SMP Muhammadiyah 4 Palembang, but three people were chosen as subjects to be interviewed. The data collection techniques in this study were questionnaires, tests, and interviews. The instrument in this study is the researcher and assisted by questionnaires, numeracy questions, and interview guidelines. The data analysis technique of this research is quantitative and qualitative with the stages of quantitative data analysis. The results showed that the response of students to blended learning was good. The numeracy ability of students after being given blended learning on fractional numbers is still low. This can be seen from the results of the written test which showed that there were only 2 students in the high category, 6 in the medium category, and 23 in the low category. Based on the results of written tests and interviews that have been analyzed based on indicators of numeracy skills, students are able to using various numbers or mathematical symbols related to basic mathematics and able to analyze information displayed in various forms (graphs, tables, charts, diagrams). This can be seen in students who are able to use mathematical concepts and procedures on fractional number material. Most of the students are not able interpret the results of the analysis to predict and make decisions, because students are not used to reinterpreting the results of calculations into the context of the problem